Fault root cause tracing of complicated equipment based on fault graph. (February 2013) - Huang, Xinlin; Gao, Jianmin; Jiang, Hongquan; Gao, Zhiyong; Chen, Fumin
Fault root causes tracing of complicated equipment in modern process industry is very important for accident and economic loss prevention. Due to the structure complexity of complicated equipment, failures happen from small parts and propagate through complex pathways often leading to serious system faults. These kind of faults caused by non-critical parts account for a large part of all the faults of complicated equipment and often cannot get enough attention in fault diagnosis. In order to trace the root causes of this kind of fault, the failure dependent relationship and fault propagation mode must be modeled accurately and effectively. Fault graph proposed by H. P. Alesso is a useful tool to represent complex structure and fault propagation pathway of complicated equipment with a special kind of fault-oriented directed graph expanded from fault tree. Fault graph takes advantage of graph rather than tree to describe complex relation between failure modes of components, and uses logic connectives to connect failure modes with logical relationship. Based on the basic concept of fault graph introduced by H. P. Alesso, this article focuses on the issues of fault graph constructing and fault graph fault root causes deducing. A fault graph constructing method was firstly discussed which uses the results of failure mode and effects analysis and the mathematical tool of polychromatic matrix and can be easily performed with the least manual work. Then the fault root causes deducing method of fault graph was investigated which focuses on fault graph reachability calculation and fault propagation pathway searching. The fault graph reachability calculation is put forward from doubletons to multiple root causes so that the reachabiltiy of any steps of fault graph pathway can be calculated. The fault propagation pathway searching method can be performed to reveal the detailed fault propagation pathway. A case study of fault graph modeling and fault root causes analysis based on fault graph of a certain type of centrifugal compressor which has complex internal structure is introduced. The case study shows that the proposed method is effective for fault root cause tracing of complicated equipment.